A zein coacervate biomaterial and its time-dependant behaviour - Timothy Quek (2020)
© 2019 Elsevier Ltd. All rights reserved. Zein is a corn-derived protein which has potential as a biomaterial for use in bone surgery. A zein coacervate, in the form of a visco-elastic solid, is proposed for use in other bone-related applications. Unlike other low-cost natural-derived materials such as chitosan and gelatin, zein is insoluble in water. This enables it to perform as a substitute for bone wax, as well as a bone filler which undergoes slow degradation. Two methods for producing the non-adhesive resinous substance are described: either directly through adding zein powder into an ethanol-water solution, or indirectly through dissolving zein into solution before coacervation upon further addition of water. Zein coacervate samples are then analysed for changes in properties with time. Loss of mass from the resinous substance is attributed to the evaporation of ethanol and water; this was measured for up for 20 minutes. Rheometeric stress sweeps performed at 0, 10, and 20 minutes after its preparation indicate that the visco-elastic material became harder with time, and more force would be required to deform the material. Finally, in vitro degradation was carried out by immersing zein samples in fluid containing lysozyme. The results suggest that the zein coacervate may be easily manipulated for up until about 10 minutes after preparation, and would degrade in vivo within a matter of weeks.